Ecological diversification is risk reducing and economically profitable – The case of biomass production with short rotation woody crops in south German land-use portfolios. (March 2017) - Hauk, Sebastian; Gandorfer, Markus; Wittkopf, Stefan; Müller, Ulrike K.; Knoke, Thomas
Abstract: As bioenergy plants, short rotation woody crops (SRWC) feature high biomass productivity and provide positive external effects, such as reduced soil erosion, increased soil life, and reduced nitrate leaching. However, they are not widespread in intensive cropping systems due to long investment periods and perceived economic disadvantages (low profitability and high risk). Nevertheless, the perceived uncertainty as the main barrier of adoption has not been addressed sufficiently, since the economic risk of SRWC has not been quantified and compared with conventional crops extensively. Another shortcoming of recent economic evaluations is that they are based on mutually exclusive comparisons of alternative investments. In fact, SRWC can be considered an asset of agricultural portfolios, whereby diversification effects are expected due to different ecology, products, and markets. To address these shortcomings, we quantified the economic risk of SRWC and conventional crops and applied the Modern Portfolio Theory to evaluate the economic diversification effects of SRWC at the farm level in a low- and a high-yielding study region in Bavaria (Germany). In SRWC-crop comparisons, SRWC showed the lowest economic risk of all crops compared and gross margins which were competitive with most alternative crops. Furthermore, the correlation of the gross margins of SRWC and agricultural crops compared was relatively low. Therefore, the inclusion of SRWC into existing farm production plans offered economic diversification, increasing the profitability at farm scale, while lowering risk. Thus, diversifying cash crop rotations with SRWC is an effective risk-management instrument that can furthermore provide positive external effects. Highlights: SRWC showed the lowest economic risk of all crops compared. In many years SRWC was economically competitive. A portfolio analysis complemented mutually exclusive crop comparisons. As complementary asset of agricultural portfolios SRWC offered. Economic diversification - increasing the profitability while lowering risk.